Evaluation of the Knowledge Management Mechanisms of Brazilian Northeast Universities Hospital Portals - Hekis, Helio Roberto; Sousa, Kleber Cavalcanti; Diogenes, Jamil Ramsi Farkat; Valentim, Ricardo Alexsandro de Medeiros; Ferreira, Luis Miguel Domingues Fernandes (Future Studies Research Journal: Trends and Strategies, 2013)
Hospital portals that manage health related data are becoming increasingly popular since they play an important role to provide, acquire and exchange information to its users. This study aims to verify how the hospital portals are contributing to the expansion of users knowledge by the analysis of interactive features associated with three mechanisms of knowledge management: Knowledge Access (KA); Knowledge Creation (KC); and Knowledge Transfer (KT). The study is exploratory, descriptive and qualitative, classified as a survey, and involves the standardization of data collection instruments (questionnaires and interviews) applied directly to people of a particular population to evaluate the knowledge management the portals present on the university hospitals from northeastern of Brazil. The results indicated that the proceeds of access to knowledge (AK) prevailed over other confirming the results found on the Asians and Americans hospital portals.